A Visual Environment Integrating Design, Implementation and Debugging in Parallel Real-Time Systems - Morón, Célio E.; Ribeiro, José R. P.; Saito, José Hiroki; Sawant, Hanumant S.; Rosa, Reinaldo R. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2000)
Due to the culture of sequential programming, the lack of tools and the inherent difficulties of parallel programming, most programmers find hard to design and evaluate parallel real-time programs. As a result, a major problem found in the development of parallel real-time systems is the difficulty to produce rapid prototypes of the application, and quite often, the development of this kind of systems is behind schedule. This work is part of a bigger project financed by FINEP, with the title “Arquitetura Paralela Usando DSPs” (Parallel Architecture Using DSPs), whose aim is to use a parallel system for processing and visualising tomographic images from the solar atmosphere in real time. In this way, it can be possible to have the 3D reconstruction of the solar corona, from the angular tomography, as well as from the spectral one. This paper presents a Visual Environment which should be able to provide continuity in the development of projects using the most common development methods, traditional or object-oriented, by offering support during the phases of implementation, debugging and testing. The environment has a visual interface and the main aim is to facilitate the development process and debugging of source code of applications developed for parallel kernels, in particular for Virtuoso (Virtual Single Processor Programming System - Virtuoso is a trademark of Eonic Systems - http://www.eonic.com ). The environment is composed by four tools: a Parallel Programs Generator, a Worst Case Execution Time Analyser, a Scheduling Analyser, and a Parallel Debugger. The first version of the tool is available for download from  http://www.dc.ufscar.br/~tev and was released as Teaching Environment for Virtuoso (TEV).